Genetic Causes Of Male Infertility: Diagnostic Significance Of DAZ Gene Cluster Analysis In Azoospermia - Purohit, Gopal Krishna; Patro, Phalguni; Pradhan, Gyanendra; Samantaray, Satyanarayan; Behera, Shreeram (Journal of Neonatal Surgery, 2025)
Male infertility is a global health concern, and genetic factors play a crucial role in its etiology. Deletions in the DAZ (Deleted in Azoospermia) gene cluster, located on the AZFc region of the Y chromosome, have been identified as a primary cause of spermatogenic failure. The DAZ gene family, comprising DAZ1, DAZ2, DAZ3, and DAZ4, encodes RNA-binding proteins that are essential for germ cell development and spermatogenesis. Studies have shown that complete or partial deletions of the DAZ gene cluster occur in 5–13% of men with non-obstructive azoospermia or severe oligozoospermia. These deletions disrupt sperm production and lead to impaired fertility. However, advances in assisted reproductive technologies, including testicular sperm extraction (TESE) with intracytoplasmic sperm injection (ICSI), have enabled men with DAZ deletions to achieve biological parenthood. The evaluation of male infertility now incorporates genetic screening for Y chromosome microdeletions, including the DAZ gene cluster. PCR-based assays targeting sequence-tagged sites (STSs) within the AZFc region allow precise identification of DAZ deletions. These analyses facilitate accurate diagnosis and guide clinical decisions regarding fertility treatment options. The assessment of DAZ gene cluster integrity remains crucial in the diagnostic workup of azoospermic men. Understanding the genetic basis of spermatogenic failure through DAZ analysis enhances our ability to provide targeted management strategies. Future research on DAZ gene function and regulation may offer new therapeutic approaches for male infertility.